Efeitos da corticoterapia pré-natal e durante a puberdade sobre a morfofisiologia do lobo ventral da próstata de ratos senis - Leonelli, Carina [UNESP] (2014)
Studies have suggested that glucocorticoids (GCs) excess during critical developmental time windows can alter reproductive parameters. Despite of the key function of the prostate in the reproductive success, and its high susceptibility to develop lesions in an age-dependent manner, the impact of early GCs excess on the gland homeostasis is still unknown. In the present study, we have investigated the effects of prenatal (PRE), peripubertal (PU) corticotherapy, and its combination (PRE+PU=REE), on aging prostate´s morphophysiology. Pregnant Wistar rats received betamethasone (0.1mg/kg/day, i.m.), or saline, on the gestational days 12, 13, 18 and 19. Male descendents received betamethasone (7mg/kg/day, gavage), or saline, from 35th to 50th postnatal day (PND35-50). Late in life (PND300), all animals were euthanized, blood samples were taken for hormones levels estimation, and the ventral prostate (VP) was excised and processed for morphology evaluation, and for proteins (AR, GR, PAR-4 and PCNA) quantification and localization as well. Lower testosterone and insulin levels were detected in group PRE, while only insulin serum levels was reduced in group PU, and no additional decrease was seen in REE. An increasing trend in the apoptosis index and metaplastic epithelium acini incidence was observed along the treated groups. The protein quantifications showed a decreased AR expression in PRE, higher proliferation marker (PCNA) expression in REE, and no significant difference in the expression of the apoptosis marker PAR-4 was detected among the groups. The immunolocalization of GR indicated a higher receptor expression in epithelial cells of treated groups, when compared to NE. Based on these results, we suggest that the corticotherapy with betamethasone during late pregnancy can program fetal prostate, resulting in altered androgen and glucocorticoids signaling permanently. Peripubertal corticotherapy deflagrated cell ...